A homozygous deleterious CDK10 mutation in a patient with agenesis of corpus callosum, retinopathy, and deafness. Issue 1 (12th November 2017) - Guen, Vincent J.; Edvardson, Simon; Fraenkel, Nitay D.; Fattal‐Valevski, Aviva; Jalas, Chaim; Anteby, Irene; Shaag, Avraham; Dor, Talia; Gillis, David; Kerem, Eitan; Lees, Jacqueline A.; Colas, Pierre; et al.
Abstract : The primary cilium is a key organelle in numerous physiological and developmental processes. Genetic defects in the formation of this non‐motile structure, in its maintenance and function, underlie a wide array of ciliopathies in human, including craniofacial, brain and heart malformations, and retinal and hearing defects. We used exome sequencing to study the molecular basis of disease in an 11‐year‐old female patient who suffered from growth retardation, global developmental delay with absent speech acquisition, agenesis of corpus callosum and paucity of white matter, sensorineural deafness, retinitis pigmentosa, vertebral anomalies, patent ductus arteriosus, and facial dysmorphism reminiscent of STAR syndrome, a suspected ciliopathy. A homozygous variant, c.870_871del, was identified in the CDK10 gene, predicted to cause a frameshift, p.Trp291Alafs*18, in the cyclin‐dependent kinase 10 protein. CDK10 mRNAs were detected in patient cells and do not seem to undergo non‐sense mediated decay. CDK10 is the binding partner of Cyclin M (CycM) and CDK10/CycM protein kinase regulates ciliogenesis and primary cilium elongation. Notably, CycM gene is mutated in patients with STAR syndrome. Following incubation, the patient cells appeared less elongated and more densely populated than the control cells suggesting that the CDK10 mutation affects the cytoskeleton. Upon starvation and staining with acetylated‐tubulin, γ‐tubulin, and Arl13b, the patient cells exhibited fewer and shorter cilia than control cells. These findings underscore the importance of CDK10 for the regulation of ciliogenesis. CDK10 defect is likely associated with a new form of ciliopathy phenotype; additional patients may further validate this association.